2008
DOI: 10.1007/s00213-008-1155-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cortisol production by metyrapone enhances trace, but not delay, eyeblink conditioning

Abstract: We conclude that acute mild metyrapone-induced hypocortisolism facilitates hippocampus-mediated classical trace eyeblink conditioning but suppresses the extinction of cerebellum-based delay-conditioned responses. Both results may be of theoretical and clinical significance for the generation and persistence of psychosomatic symptoms in patient groups characterized by relative hypocortisolism (e.g., fibromyalgia and chronic fatigue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…If corticosterone’s effects are mediated by hippocampus, we should see deficits similar to those reported by Ivkovich and Stanton (2001) where hippocampal lesions on postnatal day 10 impaired subsequent trace eyeblink conditioning on Days 25–26 but not delay eyeblink conditioning at matching inter-stimulus intervals. In humans with hyper cortisolism, trace eyeblink conditioning deficits were observed (Grillon et al, 2004) while metyrapone- induced acute, mild hypo cortisolism facilitated trace but not delay eyeblink conditioning (Nees et al, 2008), confirming that the trace eyeblink conditioning task may be sensitive to glucocorticoid effects mediated by hippocampus.…”
Section: 0 Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…If corticosterone’s effects are mediated by hippocampus, we should see deficits similar to those reported by Ivkovich and Stanton (2001) where hippocampal lesions on postnatal day 10 impaired subsequent trace eyeblink conditioning on Days 25–26 but not delay eyeblink conditioning at matching inter-stimulus intervals. In humans with hyper cortisolism, trace eyeblink conditioning deficits were observed (Grillon et al, 2004) while metyrapone- induced acute, mild hypo cortisolism facilitated trace but not delay eyeblink conditioning (Nees et al, 2008), confirming that the trace eyeblink conditioning task may be sensitive to glucocorticoid effects mediated by hippocampus.…”
Section: 0 Introductionmentioning
confidence: 84%
“…For example, intra-hippocampal infusion of corticosterone improves memory consolidation in awake but not sleeping rats (Kelemen et al, 2014). Memory consolidation is impaired in the absence of glucocorticoids following adrenalectomy or administration of antagonists (e.g., Marin et al, 2011; Nees et al, 2008). In contrast, prolonged exposure to stressors activates GRs, which appears to impair hippocampal excitability associated with learning plasticity, altering NMDA receptor expression (Lee et al, 2003), suppressing LTP, and impairing performance on declarative and spatial memory tasks and memory retrieval (see reviews: Conrad et al, 2005; DeKloet et al, 1999; McEwen et al, 2006, 2007; Roosendaal, 2002).…”
Section: 0 General Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, cortisol administration (Kuehl et al, 2010) or endogenous secreted cortisol by social stress (Duncko et al, 2007) enhanced performance on a trace eye-blink-conditioning task in men. But another study found impairment by cortisol administration in both men and women (Nees et al, 2008), or even no effect at all (Vythilingam et al, 2006). These contradictions notwithstanding, it is important to realize that within the context of etiological models of anxiety disorders sex specific sensitivity to stressful events has been repeatedly associated with the higher prevalence of mood and anxiety disorders in women (Kessler et al, 1993; Trentani et al, 2003; Cahill, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 500-ms dark period between successive light stimuli resembles task characteristics of trace classical eyeblink conditioning, in which hippocampus functions are mandatory (Clark and Squire 1998) and which is sensitive to glucocorticoid modulation (Grillon et al 2004;Nees et al 2008;Nees et al 2010). Interestingly, contingency knowledge is required to produce effective trace eyeblink conditioning (Clark and Squire 1998), but no such contingency knowledge seems to be necessary for implicit sequence learning to occur.…”
Section: Discussionmentioning
confidence: 94%